Micromachining of micro and nano-structured metals - Horvath, M.; Nyirö, J. (НТУ "ХПІ", 2010)
The microstructure of machined metals change near the tool affected zone. This paper presents some new results concerning mirror-like surface cutting of aluminum and copper. The microstructure of aluminum and copper represents the polycrystalline mild metals with face centered cubic (fcc) crystal lattice. The examination of mirror-like surface by optical microscopy, scanning electron microscopy, electron backscattered diffraction (EBSD) and atomic force microscopy show the grain boundaries and twin boundaries, which separates two domains for different crystal orientation. Young’s modulus that depends on orientation can change considerably on these boundaries, consequently the value of elastic deformation of the layer under machined surface. This effect modified the roughness too. Aluminum and copper were cut as “conventional” micro-structured metals used in everyday practice and after so called ECAP process with nano-crystalline structure, for examining effects of crystal size on machinability and surface integrity of machined mirror surfaces. Results of these comparative experiments are discussed in this paper.
Keywords: ultraprecision machining; mirror-like surfaces; copper; aluminum; crystal; microstructure; nanostructure; dislocations; anisotropy; crystal orientation; surface integrity